Identification of Very Low-Risk Subgroups of Patients with Primary Mediastinal Large B-Cell Lymphoma Treated with R-CHOP. (17th June 2021) - Vassilakopoulos, Theodoros P.; Michail, Michail; Papageorgiou, Sotirios; Kourti, Georgia; Angelopoulou, Maria K.; Panitsas, Fotios; Sachanas, Sotirios; Kalpadakis, Christina; Katodritou, Eirini; Leonidopoulou, Theoni; Kotsianidis, Ioannis; Hatzimichael, Eleftheria; et al.
Abstract: Background: R-CHOP can cure approximately 75% of patients with primary mediastinal large B-cell lymphoma (PMLBCL), but prognostic factors have not been sufficiently evaluated yet. R-da- EPOCH is potentially more effective but also more toxic than R-CHOP. Reliable prognostic classification is needed to guide treatment decisions. Materials and Methods: We analyzed the impact of clinical prognostic factors on the outcome of 332 PMLBCL patients ≤65 years treated with R-CHOP ± radiotherapy in a multicenter setting in Greece and Cyprus. Results: With a median follow-up of 69 months, 5-year freedom from progression (FFP) was 78% and 5-year lymphoma specific survival (LSS) was 89%. On multivariate analysis, extranodal involvement (E/IV) and lactate dehydrogenase (LDH) ≥2 times upper limit of normal (model A) were significantly associated with FFP; E/IV and bulky disease (model B) were associated with LSS. Both models performed better than the International Prognostic Index (IPI) and the age-adjusted IPI by Harrel's C rank parameter and Akaike information criterion. Both models A and B defined high-risk subgroups (13%–27% of patients [pts]) with approximately 19%–23% lymphoma-related mortality. They also defined subgroups composing approximately one-fourth or one-half of the patients, with 11% risk of failure and only 1% or 4% 5-year lymphoma-related mortality. Conclusion: The combination of E/IV with either bulky disease or LDH ≥2 times upper limit of normal defined high-risk but not very-high-risk subgroups. More importantly, their absence defined subgroups comprising approximately one-fourth or one-half of the pts, with 11% risk of failure and minimal lymphoma-related mortality, who may not need more intensive treatment such as R-da-EPOCH. Implications for Practice: By analyzing the impact of baseline clinical characteristics on outcomes of a large cohort of patients with primary mediastinal large B-cell lymphoma homogeneously treated with R-CHOP with or without radiotherapy, we developed novel prognostic indices which can aid in deciding which patients can be adequately treated with R-CHOP and do not need more intensive regimens such as R-da-EPOCH. The new indices consist of objectively determined characteristics (extranodal disease or stage IV, bulky disease, and markedly elevated serum lactate dehydrogenase), which are readily available from standard initial staging procedures and offer better discrimination compared with established risk scores (International Prognostic Index [IPI] and age-adjusted IPI). Abstract : This article presents data on a large number of patients with primary mediastinal (thymic) large B-cell lymphoma and reports a powerful prognostic factor analysis to identify high- or low-risk risk subgroups for risk-adapted therapy.